Drinking water and sanitation sector of Orissa: Further tasks - Mohanty, Bijoyini (2005)
Access to drinking water is a real challenge. In India, both urban and rural drinking water and sanitation projects face official obstruction in spending, monitoring progress, creating linkages. Policies and programmes may be ineffective in a setting of worsening livelihood of poor communities when there may siphon an elite capturing capitals and resources. Target driven approach in these circumstances is failure. The increase in allocation does not see proportionate sustainability of resources. There are concerns on groundwater and surface water sustainability - inequity in access in both rural and urban sectors. -Reproduced.
Keywords: Sanitation - India - Orissa; Drinking water - India - Orissa; Sanitation; Drinking water